2004
DOI: 10.1161/01.cir.0000143081.13042.04
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Mediates Staphylococcus aureus –Induced Myocardial Dysfunction and Cytokine Production in the Heart

Abstract: Background-Staphylococcus aureus sepsis is associated with significant myocardial dysfunction. Toll-like receptor 2 (TLR2) mediates the inflammatory response to S aureus and may trigger an innate immune response in the heart. We hypothesized that a TLR2 deficiency would attenuate S aureus-induced cardiac proinflammatory mediator production and the development of cardiac dysfunction. Methods and Results-Wild-type and TLR2-deficient (TLR2D) mice were studied. S aureus challenge significantly increased tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
79
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 26 publications
4
79
3
4
Order By: Relevance
“…A pathogenic ligand stimulation of TLR2, TLR4, TLR5, and TLR9 can lead to the activation of the NF-B pathway and cardiomyocyte contractile dysfunction (17,81,169). The two most-studied TLRs in the heart are TLR2 and TLR4 (41,79,80,109,169). Animal studies have indicated that these receptors are in part responsible for cardiac dysfunction in certain pathological conditions characterized in either gram-negative or gram-positive bacterial infection, such as endotoxemia (79,109), peptidoglycan-associated lipoprotein (169), and staphylococcus aureus (80).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A pathogenic ligand stimulation of TLR2, TLR4, TLR5, and TLR9 can lead to the activation of the NF-B pathway and cardiomyocyte contractile dysfunction (17,81,169). The two most-studied TLRs in the heart are TLR2 and TLR4 (41,79,80,109,169). Animal studies have indicated that these receptors are in part responsible for cardiac dysfunction in certain pathological conditions characterized in either gram-negative or gram-positive bacterial infection, such as endotoxemia (79,109), peptidoglycan-associated lipoprotein (169), and staphylococcus aureus (80).…”
mentioning
confidence: 99%
“…The two most-studied TLRs in the heart are TLR2 and TLR4 (41,79,80,109,169). Animal studies have indicated that these receptors are in part responsible for cardiac dysfunction in certain pathological conditions characterized in either gram-negative or gram-positive bacterial infection, such as endotoxemia (79,109), peptidoglycan-associated lipoprotein (169), and staphylococcus aureus (80). In the absence of a pathogen, an insult induced by transient tissue hypoxia and ischemia can induce a dramatic innate immune response in the myocardium, which has an adverse impact on cardiac anatomy and function.…”
mentioning
confidence: 99%
“…99 In a S. aureus-induced septic mouse model, cardiac dysfunction was associated with increased myocardial TNFa-and IL-1β-synthesis and was observed only in TLR2-expressing WT, but not in TLR2-deficient mice. 100 Thus, in this model deficiency of TLR2 exerted a protective effect associated with decreased levels of TNFa and IL-1β. Cardiac performance of isolated rat hearts perfused with purified staphylococcal LTA has been shown to be depressed via activation of myocardial TNFa synthesis.…”
mentioning
confidence: 73%
“…При интраназальном вве-дении бактерий Staphylococcus aureus нокаутным мышам (Tlr2 -/-) бактериальное носительство золо-тистого стафилококка в носоглотке развивалось в 10 раз чаще, чем у мышей дикого типа [30]. У но-каутных мышей (Tlr2 -/-) во время стафилококко-вой инфекции наблюдается достоверно меньший уровень продукции IL-1β и TNF-α, чем у мышей дикого типа [51]. В то же время TLR2-дефицитные макрофаги сохраняют способность продуцировать значительные объемы цитокинов.…”
Section: Tlr2unclassified
“…Представляет интерес вероятность существова-ния у TLR2 протективной роли, предупреждающей развитие дисфункции миокарда, ассоциированной со стафилококковой инфекцией [51].…”
Section: Tlr2unclassified